Students’ critical thinking skills and academic achievements in basic biology course: correlation-based analysis - Nur Hayati; Nur Kuswanti (JPBIO (Jurnal Pendidikan Biologi), 2021)
Critical thinking has become an important discussion over the last few decades and it is required skills of the 21st century. Critical thinking is thought to play a role in determining student success in education related to their academic achievement. The purpose of this study is to explain the correlation between critical thinking skills and students’ academic achievement in the natural science education department, Universitas Hasyim Asy'ari Tebuireng Jombang. This research is a quantitative research with a correlation method which was conducted in the even semester of 2018/2019. The research sample taken was 57 students who had taken a Basic Biology course. The instrument used in the research is in the form of descriptive questions. Data were analyzed descriptively quantitative with correlation product moment analysis and continued with the ANOVA test. The research results show that there is a correlation between critical thinking skills and students’ academic achievement. The contribution of critical thinking to academic achievement is 66.8% with the regression line equation Y= -37,652 + 30,177 X.